(untitled) (Pesquisa Odontológica Brasileira, 2002)
The aim of this study was to evaluate, in vitro, the effect of nicotine on the viability and morphology of fibroblasts from a continuous lineage. Two experimental groups were prepared, with different drug dosages (0 - control, 10 mug, 100 mug, 0.5 mg, 1 mg) and conditioning time (1 and 24 hours). Twelve-well microplates were utilized. Each well received 2 ml of fresh culture medium and 1 ml of a solution containing 1 × 10(5) cells/ml. Nicotine was then added to the wells, at the tested concentrations. After the incubation period, cell viability was assessed by means of 0.4% trypan blue staining. Cell viability and morphology were assessed in an inverted microscope, by a single examiner, who was blind as to the experimental groups. The experiment was repeated 5 times. Regarding morphology, in the 1-hour conditioned group there was statistically significant difference between the control group and the group with the greatest dose of nicotine. These differences were also observed between the control group and all nicotine groups after 24 hours. The results of the Kruskal-Wallis test revealed that more unviable cells were found in the groups exposed to nicotine, in comparison with the control group, both after 1 and 24 hours of conditioning (p < 0.05). Moreover, with increasing doses of nicotine there was a directly proportional increase in the number of unviable cells, both after 1 and 24 hours of exposure (p = 0.0053 and p = 0.00001, respectively). The conclusion of this study is that nicotine can alter, in vitro, the viability and morphology of fibroblasts in a manner proportional to the dose and time of exposure.